Experience Of Nurses In Providing Emergency Services In Ponelo Island: A Qualitative Study - Pomalango, Zulkifli B. (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
An emergency involves many aspects, such as health workers, families, medical equipment and adequate health service facilities. The nurse is a health worker who can save a patient's life. Emergency services in remote areas allow nurses to face several threats and challenges. The community has the view that a nurse must be able to provide all health services in a complete manner, including treatment. This study aims to explore the experiences of nurses in emergency services in the Ponelo Islands, North Gorontalo district. The research design used was qualitative with an interpretive phenomenology approach. In-depth interviews with informants, which involved 3 participants who acted as implementing nurses at the community health center in Ponelo Island area. This study resulted in four themes, namely having concern for patients who need help, the helplessness of nurses to perform first aid in emergency cases, feeling anxious when referring patients and the importance of developing quality resources and medical center service facilities. The conclusion of the results of this study is that the limited number of nurses, the lack of development through training in emergency services and inadequate public health center service facilities causes the implementation of emergency services to be not optimal.Abstrak: Keadaan darurat melibatkan banyak aspek, seperti tenaga kesehatan, keluarga, peralatan medis dan fasilitas pelayanan kesehatan yang memadai. Perawat sebagai salah satu tenaga kesehatan yang dapat menyelamatkan nyawa pasien. Layanan darurat di daerah terpencil memungkinkan perawat menghadapi beberapa ancaman dan tantangan. Masyarakat memiliki pandangan bahwa seorang perawat, harus mampu memberikan semua layanan kesehatan secara paripurna termasuk pengobatan. Penelitian ini bertujuan untuk mengeksplorasi pengalaman perawat pelaksana dalam pelayanan gawat darurat di daerah kepulauan ponelo kabupaten gorontalo utara. Desain penelitian yang digunakan adalah kualitatif dengan pendekatan fenomenologi interpretatif. Wawancara mendalam menggunakan pertanyaan semi struktur yang melibatkan 3 partisipan yang berperan sebagai perawat pelaksana di pusat kesehatan masyarakat daerah kepulauan ponelo. Penelitian ini menghasilkan empat tema yaitu mempunyai kepedulian terhadap pasien yang membutuhkan pertolongan, ketidak berdayaan perawat melakukan pertolongan pertama pada kasus gawat darurat, perasaan cemas saat merujuk pasien dan pentingnya pengembangan kualitas sumber daya dan fasilitas layanan pusat kesehatan masyarakat. Kesimpulan hasil penelitian ini adalah keterbatasan tenaga perawat, kurangnya pengembangan melalui pelatihan layanan gawat darurat dan fasilitas layanan pusat kesehatan masyarakat yang kurang memadai menyebabkan pelaksanaan layanan gawat darurat menjadi tidak optimal.